THE IMPACT OF MEDIA DIGITALIZATION ON POLITICAL COMMUNICATION IN SERBIA - Belacic, Aleksandra; Alčaković, Slavko (The European Journal of Applied Economics, 2024)
Politics-related communication is exceptionally significant as the messages sent to the electorate have a decisive influence on the formation of their stances on political matters and figures, electoral participation, and, thus, elections outcome. The present study aims to provide insight into contemporary digital political communication in Serbia by exploring voter preferences regarding obtaining political information through television and print media as well as official websites and social networks owned by broadcasters. The majority of existing academic papers belonging to the field of digital political communication emphasise the importance of digital technologies for shaping voters’ attitudes and structuring political campaigns, assuming, as a fact, the willingness of citizens to obtain information primarily through the digital sphere. We have recognised the importance of investigating the significantly under-researched process of shifting citizens’ attention from traditional to digital media. Thus, we set up a research hypothesis stating that contemporary political communication should be executed mainly digitally. Our hypothesis was evaluated by means of an exploratory study based on a series of questions related to respondents’ habits regarding political information acquisition through all relevant traditional or digital media operating in Serbia. The raw data were coded to be imported to SPSS and quantitatively analysed using descriptive statistic measures, i.e., minimum, maximum, mean, standard error and standard deviation. The subsequent qualitative analysis convinced the authors that the hypothesis should be accepted since the respondents undoubtedly prefer to obtain political knowledge via the Internet, although still inclined to be informed through traditional media as well.